Capital culturel et inégalités sociales Morales de classes et destinées sociales - Liénard, Georges (Bibliothèque idéale des sciences sociales, 2022)
The (re)publication in the Bibliothèque idéale des Sciences Sociales (Bi2S) of the work of Georges Liénard and Émile Servais finally brings to the attention of the scientific community an unjustly unknown investigation. Indeed, although it was published in 1978 in Belgium by Vie Ouvrière, this book has not circulated much in France. It is therefore practically a question of giving access to it for the first time. The book is the result of a sociology thesis carried out by two researchers, and it reports on one of the first surveys on the socialization of children conducted in the homes of families from different social classes. The new preface by Stéphane Bonnéry, after the original one by Jean Remy and Jean-Claude Chamboredon, as well as the afterword by Georges Liénard, Éric Mangez and Hugues Draelants, underline its precursory character for the sociology of education and children. A study of the variation in forms of socialization according to social position, the book is an attempt to link an ethnography of educational practices in different classes and a sociology of class morals. From the description of socialization, the temporal perspective in which it takes place, the representations of the objective future that it implies, the view of work and the social position of the family that accompanies it, the sociological analysis tends to show how social learning is also an apprenticeship of social position, and how socialization is an internalization of social status.